(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to study the impact of green accounting on investors’ decisions in some economic units in the Iraqi Stock Exchange. To achieve the research goal, the researchers relied on collecting data on the practical side by designing a questionnaire and submitting it to the research sample (financial managers, accountants, internal auditors, and investors). In some companies registered in the Iraq Stock Exchange. Various statistical methods were used for the purpose of extracting results related to the research title, and three approaches were used: the inductive, descriptive, and analytical approaches. The researchers reached the most important conclusions, the most important of which is that the economic units calculating the environmental costs affecting the environment and disclosing them in their financial statements will improve the image of these units among users of accounting information in general and investors in particular. According to the statistical results, it was found that there is an effect with direct (positive) statistical significance. ) for green accounting in investor decisions.